Microalgae as a feedstock for biofuels - Gouveia, Luisa; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
This Brief provides a concise review of the potential use of microalgae for biofuel production. The following topics are highlighted: the advantages of microalgae over conventional biofuel-producing crops; technological processes for energy production using microalgae; microalgal biomass production systems, production rates and costs; algae cultivation strategies and main culture parameters; biomass harvesting technologies and cell disruption; CO2 sequestration; life cycle analysis; and algal biorefinery strategies. The conclusions section discusses the contribution of the technologies described to environmental sustainability and future prospects.
Introduction -- Microalgae and biofules production -- Microalgal biomass production -- algal cultivation -- CO2 sequestration -- Microalgal biomass harvesting -- Cell disruption -- Production rates, production and processing costs -- Life cycle analysis -- Modelling approaches -- Algal biorefinery strategy -- Conclusions.
Electronic reproduction.
Keywords: Microalgae -- Biotechnology; Biomass energy; Biomass chemicals; Electronic books